2018
DOI: 10.1073/pnas.1810553115
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation in the hippocampus affects IGF1 receptor signaling and contributes to neurological sequelae in rheumatoid arthritis

Abstract: SignificanceAberrant insulin-like growth factor 1 receptor (IGF1R)/insulin receptor signaling in brain has recently been linked to neurodegeneration in diabetes mellitus and in Alzheimer’s disease. In this study, we demonstrate that functional disability and pain in patients with rheumatoid arthritis (RA) and in experimental RA are associated with hippocampal inflammation and inhibition of IGF1R/insulin receptor substrate 1 (IRS1) signal, reproducing an IGF1/insulin-resistant state. This restricts formation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 74 publications
(95 reference statements)
1
39
0
Order By: Relevance
“…The unsupervised clustering of the IGF1-related proteins proposed the high CVR signature, which combined the low expression of IGF1, IRS1, and IRS2 with high serum IL6, insulin and plasma glucose and emphasized the functional role of serum IGF1 in the development of early CVD in RA. These findings are in line with our recent report in experimental arthritis, which puts forward the role of excessive inhibitory phosphorylation in IRS1 to create a condition of insulin/IGF1 resistance [35]. The situation seems more complex in patients, where low IGF1 is concurrent with high IGF1R and low adaptors IRS1/2.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The unsupervised clustering of the IGF1-related proteins proposed the high CVR signature, which combined the low expression of IGF1, IRS1, and IRS2 with high serum IL6, insulin and plasma glucose and emphasized the functional role of serum IGF1 in the development of early CVD in RA. These findings are in line with our recent report in experimental arthritis, which puts forward the role of excessive inhibitory phosphorylation in IRS1 to create a condition of insulin/IGF1 resistance [35]. The situation seems more complex in patients, where low IGF1 is concurrent with high IGF1R and low adaptors IRS1/2.…”
Section: Discussionsupporting
confidence: 90%
“…It contributes to joint inflammation and affects homeostasis in chondrocytes, leukocytes and synovial fibroblasts [3133]. It has been shown that inflammation is directly related to high expression of IGF1R in leukocytes [34], which might be responsible for higher pain perception in RA [33, 35]. In a study combining two independent RA cohorts, we demonstrated that smoking and inflammation had additive suppressive effects on serum IGF1 levels [36].…”
Section: Introductionmentioning
confidence: 95%
“…In conjunction with its glycoprotein receptor (IGF-1R), IGF-1 is a phylogenetically ancient neurotrophic hormone and plays crucial roles in central nervous system development and maturation (Dyer et al, 2016). In astrocyte from mice, two previous studies demonstrated that cognition is influenced by IGF-1 by exhibiting expression of IGF-1R (Logan et al, 2018; Chen et al, 2019), as supported by both in animal and in clinical experiments (Baker et al, 2012; Andersson et al, 2018).…”
Section: Discussionmentioning
confidence: 65%
“…In AIA, a slight increase in the proliferation of neural progenitor cells and the number of surviving newly generated neurons were described (71,72). In contrast, Andersson et al recently showed reduced adult hippocampal neurogenesis and smaller hippocampal volume in mice with CIA (61). Impaired adult hippocampal neurogenesis was mediated by inflammation-induced insulin-like growth factor 1 receptor (IGF1R) signaling.…”
Section: Structural Alterations and Neuronal Dysfunction In Ramentioning
confidence: 99%